Analisis Frasa Nomina Dalam Cerita Alkitab 5 Gadis Pintar Dan 5 Gadis Bodoh - B, Lumoindong (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This study analyzes the use of noun phrases in the article titled "5 Smart Girls and 5 Foolish Girls." The main focus of the research is to identify the form, structure, and function of the noun phrases used, as well as to examine how these phrases construct meaning within the context of the article. A qualitative descriptive method was employed to analyze the data. The results show that noun phrases in this article vary in complexity, ranging from simple to complex noun phrases with additional modifiers. Furthermore, the study finds that the choice of noun phrases contributes to reinforcing characterization, portraying emotions, and shaping the writer’s perspective on the subjects discussed. Therefore, this analysis provides a deeper understanding of the syntactic role of noun phrases in narrative discourse.